Macrophage cyclooxygenase and inducible nitric oxide synthase expression in response to copper deficiency mediated oxidative stress and conjugated linoleic acid - Iwakiri, Yasuko, author; Allen, Kenneth D., advisor; Sampson, David A., advisor; Harris, Mary, committee member; Orme, Ian, committee member (Colorado State University. Libraries, 2000)
Excessive prostaglandin E2 (PGE2) and nitric oxide (NO), which are synthesized by inducible forms of cyclooxygenase (COX-2) and nitric oxide synthase (iNOS), respectively, play key roles in pathogenesis of cancer, atherosclerosis and arthritis. I investigated the synthesis of PGE2 and NO in activated macrophages in response to copper deficiency-induced oxidative stress and conjugated linoleic acid (CLA). First, I tested the hypothesis that diets marginal (CuM) and deficient (CuD) in copper would decrease Cu, Zn-superoxide dismutase (Cu, Zn-SOD) activity and increase cellular oxidative stress, which would increase PGE2 and NO production by increasing COX-2 and iNOS expression in activated macrophages. Lipid peroxidation and intracellular superoxide levels were significantly enhanced in parallel with decreased Cu, Zn-SOD activity in both CuM and CuD groups. The CuD group, but not the CuM group, showed a significant four-fold increase in PGE2 production in activated cells accompanied by a significant five-fold increased in COX activity and four fold increase in COX-2 mRNA levels. NO was 40 % higher in the CuD group compared to the copper adequate (CuA) group, with no significant difference in iNOS expression. Second, I investigated effects of CLA and arachidonic acid (AA) on PGE2 and NO synthesis in RAW264.7 macrophages. CLA significantly depressed PGE2 and NO production by 78% and 57% compared to control values, respectively. Northern blot analysis of COX-2 and iNOS showed significant suppressive effects of CLA. AA significantly increased PGE2 synthesis by 62% compared to control values. AA also suppressed NO production and iNOS expression in the same manner as observed for CLA. These results suggest that beneficial effects of CLA may be related to its ability to decrease both PGE2 and NO synthesis by suppressing transcription of COX-2 and iNOS in activated macrophages. In conclusion, copper marginal and deficient diets increased macrophage oxidative stress. CuD up-regulates macrophage PGE2 and NO synthesis, which may favor atherogenesis. The ability of CLA to suppress both PGE2 and NO production in macrophages may play an important role in the mechanisms of anti-cancer and antiatherogenic effects of CLA.
Keywords: nutrition; cellular biology